All‐Inorganic Rare‐Earth Halide Double Perovskite Single Crystals with Highly Efficient Photoluminescence. Issue 19 (14th June 2021) - Zhang, Ruiling; Wang, Zhongyi; Xu, Xin; Mao, Xin; Xiong, Jin; Yang, Yang; Han, Keli
Abstract: Halide double perovskites have been regarded as promising alternatives to famous lead halide perovskites in the field of luminescent materials. However, the low‐emission efficiency of pristine ones and the lack of efficient blue emitters remain considerable obstacles for their applications in light‐emitting devices. Here, an air‐stable, all‐inorganic Sc‐based double perovskite Cs2 NaScCl6 is reported, which exhibits strong blue emission peaking at 445 nm with an averaged quantum yield of 29.05% (the highest reported value for pristine halide double perovskites). The rare‐earth double perovskite also shows excellent stability against heat and irradiation. Bulk perovskite Cs2 NaScCl6 can be an effective host to incorporate Mn 2+ ions, yielding interesting tunable dual broadband emission, slightly redshifted blue emission (450 nm) from the host and red emission (635 nm) from Mn 2+ d–d transitions. These findings present a new direction toward the design of high‐efficiency, stable, and environmentally friendly perovskite light emitters. Abstract : An efficient blue emitting all‐inorganic double perovskite Cs2 NaScCl6 is synthesized by using a cooling‐induced crystallization method. Mn 2+ ions can be efficiently doped into the lattice of Cs2 NaScCl6, leading to tunable dual broadband emission, a blue emission from the host and a red emission from Mn 2+ transitions. The emission mechanism is revealed by using a series of spectroscopic techniques.